Waves and Reverse Waves: Turkey Democratization After the Coup of 1960 - Fathur Rizki (NEGREI: Academic Journal of Law and Governance, 2021)
As the country that has been experiencing several changes of governmental system, especially after the coup of 1960, made Turkey as an attractive country to look at how they implement democracy. Democracy, which is the most widely used system in the world, has ups and downs in its application especially within Turkey that has long been ruled under the monarchy of Ottoman empire and republic party system, that considered as authoritarian before it leads to the coup of military. These cases refer to the development of democratization’s implementation within the country, and this paper will discuss how the waves and reverse waves of Turkey's democratization in the context of political parties’ participation in Turkish state's political stage, after the military coup in 1960 by implementing the theory of world’s democratization waves by Samuel P. Huntington. This paper also aims to analyze the development of Turkey democratization by observing several events that happened started after the military coup in 1960 and the rest until the it comes to contemporary issues by the rise of AKP party in 2002.